Prevalence of amyotrophic lateral sclerosis in the United States using established and novel methodologies, 2017. Issue 1 (2nd January 2023) - Mehta, Paul; Raymond, Jaime; Punjani, Reshma; Han, Moon; Larson, Theodore; Kaye, Wendy; Nelson, Lorene M.; Topol, Barbara; Muravov, Oleg; Genson, Corina; Horton, D. Kevin
Abstract: Objective :To estimate the prevalence of amyotrophic lateral sclerosis (ALS) in the United States for 2017 using data from the National ALS Registry (Registry) as well as capture–recapture methodology to account for under-ascertainment. Established in 2010, the Registry collects and examines data on ALS patients in the US to better describe the epidemiology of ALS (i.e. risk factor exposures, demographics). Methods: The Registry compiled data from national administrative databases (from the Centers for Medicare and Medicaid Services, the Veterans Health Administration, and the Veterans Benefits Administration) and a voluntary enrollment data through a web portal (www.cdc.gov/als ). To estimate the number of missing cases, capture–recapture methodology was utilized. Results: The Registry conservatively identified 17, 800 adult persons (lower-bound estimate) who met the Registry definition of ALS for an age-adjusted prevalence of 5.5 per 100, 000 US population. Using capture–recapture methodology, we obtained a "mean case count" of 24, 821 ALS cases (prevalence of 7.7 per 100, 000 U.S. population) and estimated the upper-bound estimate to be 31, 843 cases (prevalence of 9.9 per 100, 000 U.S. population). The pattern of patient characteristics (e.g. age, sex, and race/ethnicity) remained unchanged from previous Registry reports. Overall, ALS was most common among whites, males, and persons aged 60–69 years. The age groups with the lowest number of cases were persons aged 18–39 years. Males had a higher prevalence than females overall and across all data sources. Conclusions: Existing Registry methodology, along with capture-recapture methodology, are being used to better describe the epidemiology and demographics of ALS in the US.